Identification Phalaenopsis sp in Nglurah Village, Tawangmangu as A Source of High School Biology Learning - Muhammad Nur Hidayad; Tri Wiharti (Jurnal Biologi Tropis, 2026)
Biology learning in the Merdeka Curriculum emphasizes the use of local potential as a contextual and meaningful learning resource. Nglurah Village, Tawangmangu District, Karanganyar Regency has high potential for moon orchid (Phalaenopsis sp) diversity that has not been widely utilized as a learning resource for high school biology. This study aims to identify the types and morphological characteristics of moon orchids in Nglurah Village and explore their use as a learning resource for biology in the biodiversity material for 10th grade high school students. The research method used is direct observation with a qualitative descriptive approach. Data were collected through observation of the morphology of flowers, leaves, and roots, visual documentation, and identification of varieties with the help of Google Lens and interviews with local orchid farmers. The results of the study showed that 22 varieties of moon orchids were found with quite diverse morphological differences, including flower size, color patterns, labellum shape, and other visual characteristics. This diversity indicates an intensive hybridization process, supported by environmental conditions in Nglurah Village that are suitable for the growth of moon orchids. The findings of this study have great potential to be used as a source of high school biology learning that is relevant to the Merdeka Curriculum, particularly in the subject of biodiversity and classification of living things. The use of moon orchids as a learning object is expected to provide direct learning experiences, improve observation and classification skills, and foster students' awareness of the importance of preserving local biodiversity.